Neglected fracture tibia dextra with gangrene pedis, post treatment by traditional bone setter - Musthofa, Fuad Dheni; Suhanto, Suhanto; Marjono, Teguh (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
The patient is a 9-year-old female who comes from Oba District, Tidore island. Come to Emergency Department Ternate General Hospital with the right leg limbs which have blackened, some open wounds on the skin that give exposure to soft and hard tissue (bone). According to the alloanamnesis, before entering the hospital, she treated for three weeks in traditional bonesetter due to fractures. Given the traditional treatment of herbal concoction cream and in splints with a bamboo stick and the therapy wasn’t successful. Clinical evaluation revealed a gangrenous right leg for which she had the risk of an above knee amputation. The diagnosis was gangrene pedis dextra e.c. neglected fracture tibia dextra post-treatment by the traditional bone setter. Operative management was wound debridement and amputation I-V metatarsal. Neglected fracture is a fracture that is not handled correctly, resulting in delays in handling, worse conditions and even defects. The purpose of writing this case report is to provide an overview of the neglected case of fractures caused by traditional bonesetter.